Safety and Efficacy of Tirofiban in Severe Ischemic Stroke Patients Undergoing Mechanical Thrombectomy - Lingxin Cai; Tingting Wang; Aiqing Chen; Chenhan Ling; Jing Xu; Cong Qian; Gao Chen (Journal of Cardiovascular Development and Disease, 2022)
Tirofiban has recently shown encouraging efficacy and safety among acute ischemic stroke (AIS) patients with mechanical thrombectomy (MT). However, the benefits of tirofiban varied among studies depending on the patient’s condition, which was often not well analyzed. This study aimed to identify the characteristics of patients who may obtain the largest benefits from tirofiban. The efficacy endpoint was a favorable outcome defined as a modified Rankin Scale (mRS) score of 0~2 at 90 days. The safety endpoints were intracranial hemorrhage (ICH), symptomatic intracranial hemorrhage (sICH) and mortality at 90 days. Adjusted logistic regression analysis and subgroup analyses were utilized to investigate the factors associated with tirofiban and the outcome. All of 285 patients fit the inclusion criteria. Tirofiban was associated with a higher rate of favorable outcome (aOR 2.033, 95% CI, 1.002~4.123, p = 0.043) but not with an increased risk of ICH, sICH or mortality (p > 0.05). Moreover, subgroup analyses revealed that tirofiban was associated with favorable outcomes in patients with NIHSS > 14 (aOR 2.778, 95% CI 1.056~7.356, p = 0.038) but not in patients with NIHSS ≤ 14 (aOR 1.719, 95% CI 0.646~4.578, p = 0.278). No significant heterogeneity was found in the effect of tirofiban across the subgroups of age, sex, ASPECTS, time from onset to puncture, use of t-PA or stroke etiology (p for interaction > 0.05). The administration of tirofiban was associated with favorable outcomes in severe ischemic stroke patients, and further studies are needed to confirm this finding.